Analisis Speaking Anxiety Dalam Proses Pembelajaran Pada Mahasiswa PBI Semester 5 UIN Raden Mas Said Surakarta - Lailatul Munawaroh; Celviaulia Fitri; Anggela Kunti; Siti Nur Laila (Academica: Journal of Multidisciplinary Studies, 2022)
This study is a qualitative study where the researcher aims to observe and analyze speaking anxiety in 5th semester English Education students at UIN Raden Mas Said Surakarta. This study adopts or uses data collection techniques in the form of interviews and questionnaires. Researchers collected 14 respondent data from students majoring in English Education in semester 5 who had undergone interviews and had filled out questionnaires. Because this research uses an qualitative approach, the data analysis technique used is qualitative descriptive non-statistical. The findings show that some of the main causes of speaking anxiety in students are self-confidence, lack of vocabulary and also lack of preparation. The results of this study contribute to the field of language teaching in terms of student factors, especially speaking anxiety during classroom learning. This study aims to apply the method of overcoming speaking anxiety in the learning process in the classroom, especially English Education. Keywords: English Education; Speaking Anxiety; Students